PENGARUH KEBIASAAN MEMBACA KITAB SUCI DALAM KELUARGA KRISTIANI TERHADAP PERKEMBANGAN IMAN ANAK - Junneli, Junneli; Wilhelmus, Ola Rongan (CREDENDUM: Jurnal Pendidikan Agama, 2021)
This study uses a qualitative approach to explore the influence of reading the Bible on the development of children's faith. The main objectives of this study are to understand how reading the Bible can influence children's understanding and development of faith, as well as to explore the role of the Bible in shaping their belief in God. Based on the results of data analysis obtained from 7 respondents, it is known that all respondents (100%) stated that faith is a form of strong belief or conviction in God, which is a guideline or regulator in everyday life. This faith functions as a foundation in facing life's challenges and as a spiritual strength in their lives. In addition, this study also reveals children's understanding of the Bible. From the results of the study, 7 respondents (100%) stated that they view the Bible as a guideline for life, especially in the context of family life. Respondents see the Bible not only as a collection of teachings or stories, but as a source of values ​​and guidance in living a harmonious and loving family life. In essence, the Bible is indeed a guideline for life for Catholics. Through reading and deep understanding of the Bible, these children can absorb teachings that lead to the development of attitudes of love, empathy, and concern for others. In these teachings, Christ's love for humanity is the main value that inspires them to live their lives with understanding and love for God and others. Overall, this study aims to describe how reading the Holy Bible can play an important role in shaping and developing children's faith, as well as strengthening their understanding of the values ​​of life taught in religious teachings.